Preparation and application of reticular silver-coated magnetic metal electromagnetic shielding material
By using the preparation method of mesh-shaped silver-covered magnetic metal in the electromagnetic shielding material, the problems of low intrinsic electromagnetic parameters and weak electromagnetic synergistic shielding effect in the prior art are solved, and excellent electromagnetic shielding performance in broadband and low frequency bands are achieved.
Patent Information
- Application Number
- CN202510044648.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-12
AI Technical Summary
In the prior art, the intrinsic electromagnetic parameters of the core-shell structure electromagnetic shielding material have low elevation and weak electromagnetic synergistic shielding effect, resulting in low shielding efficiency in broadband and low frequency bands.
The preparation method of mesh silver-covered magnetic metal is adopted, and a highly conductive carbon interface layer and mesh silver shell layer are formed through the steps of pickling, dopamine coating, electroless plating and annealing, thereby enhancing the electromagnetic coupling between the core and the shell.
It significantly improves the electromagnetic shielding performance of the material, especially in the wide frequency range, and improves the low-frequency magnetic field shielding performance.
Smart Images

Figure CN119789401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding materials, and in particular to the preparation and application of a mesh silver-coated magnetic metal electromagnetic shielding material. Background Art
[0002] Electromagnetic pollution has become a global environmental problem that cannot be ignored. Its seriousness lies in the fact that it is invisible and colorless but fills the entire space, posing a serious threat to human health, the ecological environment, and the normal operation of electronic equipment. Long-term exposure to electromagnetic radiation may lead to nervous system disorders, decreased immunity, memory loss, and even increase the risk of cancer. In addition, electromagnetic pollution can interfere with communication systems, leak private information, and even cause explosions. The importance of electromagnetic shielding materials lies in their ability to effectively block or attenuate the propagation of electromagnetic waves, limit radiation energy to a safe range, and thus reduce the hazards of electromagnetic waves. With the continuous development of science and technology, the application fields of electromagnetic shielding materials are also expanding, and their importance in military, aerospace, communications, medical and other fields is becoming more and more prominent. However, existing commercial electromagnetic shielding materials are difficult to achieve efficient electromagnetic shielding in wide frequency bands, especially in low frequency bands.
[0003] At low frequencies, electromagnetic waves exhibit quasi-static field characteristics, and the electric and magnetic field components need to be shielded separately. For low-frequency electric fields, conductive materials can still reflect low-frequency waves through impedance mismatch. However, for low-frequency magnetic fields, conductive materials can only absorb low-frequency waves through eddy current losses. The introduction of high magnetic materials can significantly increase the eddy current loss strength of electromagnetic shielding materials, thereby improving the low-frequency magnetic field shielding effect.
[0004] The prior art discloses that a magnetic bonding layer is formed on the surface of a fiber cloth by a magnetic bonding agent, the magnetic bonding agent includes a bonding agent and superparamagnetic ferroferric oxide; the surface of the magnetic bonding layer is coated with a silver coating; the silver coating is formed by in-situ reduction deposition of a silver ammonia solution, and a catalyst and a polymer for improving the adhesion of silver are provided on the surface of the magnetic bonding layer. However, the intrinsic magnetic permeability of ferroferric oxide is low, and the improvement of the low-frequency shielding effectiveness of the fiber cloth is limited.
[0005] Compared with composite methods such as grafting and mixing, the core-shell structure composite electric / magnetic composite electromagnetic shielding material has better electromagnetic coupling. Those skilled in the art use chemical plating to plate a silver shell layer on the surface of Fe3O4. However, the silver shell layer prepared by chemical plating is composed of nanosilver particles, and the high contact resistance between the particles weakens the intrinsic conductivity of the electromagnetic shielding material, resulting in a serious lack of electric field shielding effect.
[0006] The prior art also adds a nickel transition layer in the middle of the silver-coated copper powder and performs heat treatment under a protective atmosphere, so as to form intermetallic compounds through diffusion between copper, nickel and silver, and form covalent bonds between metals, thereby improving the bonding strength of the coating. At the same time, the use of nickel as an intermediate layer can, on the one hand, improve the compactness of the coating layer to improve its resistance to high-temperature oxidation. On the other hand, since nickel has good magnetic conductivity, it can improve the oxidation resistance of copper powder while also improving the ferromagnetism of the composite powder, thereby achieving magnetic shielding at low frequencies. The obtained powder has an excellent electromagnetic shielding effect in a wider frequency band. However, the lower intrinsic magnetic permeability and lower doping amount of nickel materials limit the improvement of the low-frequency electromagnetic shielding performance of the composite powder.
[0007] In summary, how to improve the electromagnetic coupling between magnetic materials and conductive materials, as well as the intrinsic electromagnetic parameters of magnetic materials and conductive materials, is the key to preparing excellent broadband or low-frequency electromagnetic shielding materials. Summary of the invention
[0008] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the problems in the prior art that the core-shell structure electromagnetic shielding material has low intrinsic electromagnetic parameters, weak electromagnetic synergistic shielding effect, and low broadband and low-frequency shielding effectiveness. The present invention provides a preparation and application of a mesh silver-coated magnetic metal electromagnetic shielding material. The method is based on the carbonization of the polydopamine coating layer, and the electromagnetic coupling between the core and the shell layer is enhanced by a highly conductive carbon layer, and finally a mesh silver-coated magnetic metal is prepared with good shielding effectiveness in a wide frequency range.
[0009] The first object of the present invention is to provide a method for preparing a mesh silver-coated magnetic metal electromagnetic shielding material, comprising the following steps:
[0010] The magnetic metal powder is acid-washed to obtain acidified magnetic metal powder;
[0011] The acidified magnetic metal powder is evenly dispersed in a Tris buffer solution, and then dopamine hydrochloride is added and the pH is adjusted to 8-9, and the reaction is carried out in the dark to obtain dopamine-coated magnetic metal powder;
[0012] The dopamine-coated magnetic metal powder is uniformly mixed with deionized water, glucose, sodium potassium tartrate, and PVP, and then a silver ammonia solution is added to react with the mixture to obtain a silver-coated magnetic metal powder;
[0013] Under vacuum, the silver-coated magnetic metal powder is heated to 200-600° C. and kept warm for 2-12 hours to obtain a mesh silver-coated magnetic metal electromagnetic shielding material.
[0014] Preferably, the magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy;
[0015] The magnetic metal powder is a flaky magnetic metal powder obtained by ball milling, and its D50 is 2 to 65 μm.
[0016] Preferably, the concentration of the Tris buffer solution is 0.05 to 0.25 mol / L;
[0017] The mass ratio of the acidified magnetic metal powder, Tris buffer solution and dopamine hydrochloride is (25-60): (400-1000): (0.4-4);
[0018] Among them, the light-avoidance reaction time is 12 to 48 hours.
[0019] Preferably, the mass ratio of the dopamine-coated magnetic metal powder to deionized water, glucose, potassium sodium tartrate, PVP and silver ammonia solution is (20-80): (300-650): (2.3-28): (0.02-2.5): (0.5-4): (200-480); wherein the concentration of the silver ammonia solution is 7.5-80 g / L; and the addition rate of the silver ammonia solution is 50-250 ml / h.
[0020] Preferably, the temperature of the mixed reaction is 20-60° C., and the reaction time is 0.2-4 h.
[0021] Preferably, the heating rate is 2-10°C / min.
[0022] Preferably, during pickling, the pH of the acid solution used is 1 to 3, and the pickling time is 3 to 10 minutes.
[0023] The second object of the present invention is to provide a mesh silver-coated magnetic metal electromagnetic shielding material.
[0024] The third object of the present invention is to provide a mesh silver-coated magnetic metal electromagnetic shielding material for use in electromagnetic shielding.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention provides a preparation method and application of a mesh silver-coated magnetic metal electromagnetic shielding material. During the annealing process, the silver nanoparticles originally on the surface of the silver-coated magnetic metal will undergo sintering, the particles will neck and link with each other, and shrink under the action of surface tension to form a mesh coating structure, thereby greatly eliminating the original contact resistance between the silver nanoparticles, thereby effectively improving the electrical conductivity of the silver-coated magnetic metal.
[0027] The present invention uses ball-milled flaky silver-coated magnetic metal as raw material. During the annealing process, the magnetic metal uses the residual stress generated by plastic deformation as a driving force to recover and recrystallize, the residual stress is significantly eliminated, and the original deformed grains (fibrous structure) are replaced by non-distorted equiaxed crystals. In addition, the grains are refined, the number of unpaired magnetic atoms increases, the deflection resistance of the magnetic dipole is reduced, and the scattering effect of defects on electron transmission is weakened, thereby achieving the simultaneous improvement of the magnetic permeability and electrical conductivity of the silver-coated magnetic metal.
[0028] The present invention is based on the carbonization of the insulating dopamine coating layer during the annealing process to form a carbon interface layer. The conductive carbon interface layer effectively improves the electromagnetic coupling between the magnetic metal and the mesh silver shell layer, further improving the electromagnetic shielding effectiveness of the material at low frequencies. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The microscopic morphology of the flaky magnetic metal in Example 1;
[0030] Figure 2 The microscopic morphology of the silver-coated magnetic metal mesh prepared in Example 4;
[0031] Figure 3 This is the microscopic morphology of the silver-coated magnetic metal prepared in Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0033] The purpose of the present invention is to provide a method for producing a mesh silver-coated magnetic metal with high electromagnetic parameters, strong electromagnetic coupling and broadband electromagnetic shielding performance. The mesh silver-coated magnetic metal provided by the present invention is mainly made of a sheet-shaped magnetic metal with a large diameter-to-thickness ratio obtained by ball milling. On the one hand, the good surface-to-surface contact of the sheet-shaped material is used to enhance the electromagnetic contact between the materials. On the other hand, the magnetic metal grains are allowed to accumulate sufficient plastic deformation to provide a driving force for the recovery and recrystallization that occurs during the annealing process. First, the magnetic metal is pickled with an acid solution to remove the oxide film layer on the surface of the magnetic metal to enhance the electromagnetic coupling between the shell layer and the core. Subsequently, the pickled magnetic metal is coated with dopamine, and a weakly reducing polydopamine layer is used to effectively and highly deposit the silver shell layer on the surface of the dopamine layer. Finally, annealing is used to sinter the nanosilver on the surface of the silver-coated magnetic metal to form a mesh interconnected structure, thereby enhancing the conductivity of the material. At the same time, the sheet-shaped magnetic metal core that has undergone a large amount of plastic deformation undergoes recrystallization annealing to improve the magnetic permeability of the material. In addition, the polydopamine coating is carbonized, and the electromagnetic coupling between the core and the shell is enhanced by the highly conductive carbon layer, and finally a mesh silver-coated magnetic metal is prepared with good shielding effectiveness in a wide frequency range.
[0034] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a mesh silver-coated magnetic metal electromagnetic shielding material, comprising the following steps:
[0035] The magnetic metal powder is pickled to obtain acidified magnetic metal powder; during pickling, the pH of the acid solution used is 1 to 3, and the pickling time is 3 to 10 minutes.
[0036] The acidified magnetic metal powder is evenly dispersed in a Tris buffer solution, and then dopamine hydrochloride is added and the pH is adjusted to 8-9, and the reaction is carried out in the dark to obtain dopamine-coated magnetic metal powder;
[0037] The dopamine-coated magnetic metal powder is uniformly mixed with deionized water, glucose, sodium potassium tartrate, and PVP, and then a silver ammonia solution is added for mixed reaction to obtain a silver-coated magnetic metal powder; the heating rate is 2 to 10°C / min. The temperature of the mixed reaction is 20 to 60°C, and the reaction time is 0.2 to 4h.
[0038] Under vacuum, the silver-coated magnetic metal powder is heated to 200-600° C. and kept warm for 2-12 hours to obtain a mesh silver-coated magnetic metal electromagnetic shielding material.
[0039] The magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy;
[0040] The magnetic metal powder is in the form of flakes, and its D50 is 2-65 μm. The magnetic metal powder is ball-milled to obtain a flake absorbent.
[0041] The concentration of the Tris buffer solution is 0.05-0.25 mol / L;
[0042] The mass ratio of the acidified magnetic metal powder, Tris buffer solution and dopamine hydrochloride is (25-60): (400-1000): (0.4-4);
[0043] Among them, the light-avoidance reaction time is 12 to 48 hours.
[0044] The mass ratio of the dopamine-coated magnetic metal powder to deionized water, glucose, potassium sodium tartrate, PVP and silver ammonia solution is (20-80): (300-650): (2.3-28): (0.02-2.5): (0.5-4): (200-480); wherein the concentration of the silver ammonia solution is 7.5-80 g / L; and the addition rate of the silver ammonia solution is 50-250 ml / h.
[0045] Exemplarily, a method for preparing a mesh silver-coated magnetic metal electromagnetic shielding material comprises:
[0046] Pickling: Mix the magnetic metal with an acid solution of a certain concentration, react for a certain period of time, centrifuge to remove the solvent, and wash with deionized water until the solvent is neutral.
[0047] Dopamine coating: The acid-washed magnetic metal was mixed with a Tris buffer solution, and then a certain amount of dopamine hydrochloride was added, and the pH of the solvent was adjusted to 8.5, and then stirred for a period of time at room temperature in the dark.
[0048] Chemical plating: The dopamine-coated magnetic metal is mixed with a certain amount of deionized water, glucose, potassium sodium tartrate, and PVP, and then a silver ammonia solution is added to the mixed system at a certain temperature. After the addition is completed, the reaction is allowed to proceed for a period of time, and then the solvent is separated by centrifugation and washed with deionized water until the solvent is neutral. The precipitate is vacuum dried to obtain a silver-coated magnetic metal powder. Glucose and potassium sodium tartrate can be used as reducing agents to reduce the silver ions in the silver ammonia solution to generate nanosilver attached to the surface of the magnetic metal. Glucose has an appropriate reduction rate, but it can be seen from the redox mechanism that the reaction during chemical plating will continuously consume OH-, causing the pH value to drop. However, the reducibility of glucose is sensitive to the pH value, so uniform reduction is achieved by compounding potassium sodium tartrate with a more stable reduction rate. PVP, as a dispersant, can avoid the agglomeration of magnetic metals on the one hand, so that their surfaces are fully infiltrated by the plating solution, and on the other hand, it can avoid the accumulation of nanosilver particles on the surface of the magnetic metal, making the coating uniform and dense.
[0049] Annealing: silver-coated magnetic powder is put into a crucible, vibrated and then put into a tube furnace, and heat treated under vacuum for a period of time to obtain a mesh-like silver-coated magnetic metal. After heat treatment, the nano silver particles sinter and shrink, and sintering necks are generated between adjacent silver particles, eventually forming a mesh-like interconnected structure.
[0050] The magnetic metal powder is one or more of an iron silicon aluminum alloy, an iron silicon chromium alloy, an iron silicon alloy, carbonyl iron, carbonyl nickel, an iron aluminum boron alloy, an iron boron phosphorus alloy, an iron nickel molybdenum alloy, an iron chromium nickel alloy, an iron nickel alloy, an iron cobalt chromium alloy, and an iron cobalt nickel chromium alloy; specifically, an iron silicon aluminum alloy (D50 = 7 μm, spherical), an iron silicon chromium alloy (D50 = 12 μm, spherical), an iron silicon alloy (D50 = 9.4 μm, spherical), a carbonyl iron (D50 = 6.7 μm, spherical), and a carbonyl nickel (D50 = 7.7 μm, spherical). D50=20μm, spherical), iron-aluminum-boron alloy (D50=6.3μm, spherical), iron-boron-phosphorus alloy (D50=4.2μm, spherical), iron-nickel-molybdenum alloy (D50=13μm, spherical), iron-chromium-nickel alloy (D50=13.4μm, spherical), iron-nickel alloy (D50=7μm, spherical), iron-cobalt-chromium alloy (D50=8.4μm, spherical), and iron-cobalt-nickel-chromium alloy (D50=12.4μm, spherical) are all purchased from Blue Ocean New Materials Co., Ltd.
[0051] A second aspect of the present invention provides a mesh silver-coated magnetic metal electromagnetic shielding material.
[0052] A third aspect of the present invention provides an application of a mesh silver-coated magnetic metal electromagnetic shielding material in electromagnetic shielding.
[0053] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0054] Example
[0055] A method for preparing a mesh-shaped silver-coated magnetic metal, the preparation process of which comprises the following steps:
[0056] Pickling: Mix the magnetic metal with an acid solution of a certain concentration, react for a certain period of time, centrifuge to remove the solvent, and wash with deionized water until the solvent is neutral.
[0057] Dopamine coating: The acid-washed magnetic metal was mixed with a Tris buffer solution, and then a certain amount of dopamine hydrochloride was added, and the pH of the solvent was adjusted to 8.5, and then stirred for a period of time at room temperature in the dark.
[0058] Chemical plating: The dopamine-coated magnetic metal is mixed with a certain amount of deionized water, glucose, sodium potassium tartrate, and PVP, and then a silver ammonia solution is added dropwise to the mixed system at a certain temperature. After the addition is completed, the mixture is reacted for a period of time, and then the solvent is centrifuged and washed with deionized water until the solvent is neutral. The precipitate is vacuum dried to obtain a silver-coated magnetic metal powder.
[0059] Annealing: Put the silver-coated magnetic powder into a crucible, vibrate it and then put it into a tube furnace. Heat treat it under vacuum for a period of time to obtain a mesh silver-coated magnetic metal.
[0060] The present invention is described in detail below with reference to the embodiments.
[0061] Firstly, the spherical magnetic metal is ball-milled to obtain the flaky magnetic metal.
[0062] The flaky magnetic metals in the embodiments of the present invention are all prepared by stirring ball milling using commercial spherical magnetic metals as raw materials. The specific method is as follows:
[0063] A certain amount of ball milling beads, anhydrous ethanol, and spherical magnetic metal are sequentially added to a stirring ball mill, stirred and ball milled at a certain speed for a period of time, then the liquid is separated and poured off, and the flaky magnetic metal is obtained after vacuum drying and precipitation. The ball milling process of each embodiment is shown in Table 1.
[0064] Table 1 Ball milling process parameters of each embodiment
[0065] Example 1 2 3 4 Raw materials used Iron Silicon Chromium Alloy Iron Silicon Aluminum Alloy Iron-Chromium-Nickel Alloy Iron Nickel Molybdenum Alloy D50(μm) 12 7 13.4 7 Ball mill mass (kg) 10 12 15 18 Anhydrous ethanol mass (kg) 2.5 2.5 3 2.5 Mass of magnetic absorbent (kg) 1.5 0.5 1.5 1 Ball mill speed (rpm) 160 240 180 200 Ball milling time (h) 14 18 12 16
[0066] The microscopic morphology of the flaky magnetic metal obtained in Example 1 is as follows: Figure 1 As shown, it can be seen that the flake metals are all in flaky form after ball milling and are not broken due to stress concentration.
[0067] Pickling: The flaky magnetic metal is pickled. The specific process parameters are shown in Table 2.
[0068] Table 2 Pickling process parameters of each embodiment
[0069] Example 1 2 3 4 Acid type Dilute hydrochloric acid Dilute sulfuric acid Dilute sulfuric acid Dilute hydrochloric acid pH 1.5 2 1.5 2 Reaction time (min) 3 3 5 6
[0070] Dopamine coating: The pickled flaky magnetic metal is coated with dopamine. The specific process parameters are shown in Table 3.
[0071] Table 3 Dopamine coating process parameters of each embodiment
[0072] Example 1 2 3 4 Flake magnetic metal (parts) 30 25 40 50 Tris buffer solution concentration (mol / L) 0.1 0.05 0.15 0.2 Tris buffer solution (parts) 600 1000 800 1000 Dopamine hydrochloride (part) 0.5 1.2 1.6 2 Reaction time 12 12 24 48
[0073] Chemical plating: The dopamine-coated flaky magnetic metal is chemically plated to prepare a silver-coated magnetic metal. The specific process parameters are shown in Table 4.
[0074] Table 4 Chemical plating process parameters of each embodiment
[0075] Example 1 2 3 4 Dopamine coated magnetic metal (parts) 45 50 70 40 Deionized water (parts) 345 420 500 370 Glucose (parts) 15 18 21 25 Potassium sodium tartrate (part) 2.4 2.0 2.0 2.1 PVP(share) 1 1.2 1.5 1.2 Silver ammonia solution (parts) 250 350 280 400 Silver ammonia solution concentration (g / L) 54 25 40 18 Reaction temperature 35 40 40 50 Reaction time 2 0.5 2 0.5 Silver ammonia solution drop rate 50 100 150 100
[0076] Annealing: The silver-coated magnetic metal after chemical plating is annealed. The specific process parameters are shown in Table 5.
[0077] Table 5 Annealing process parameters of each embodiment
[0078] Example 1 2 3 4 Heating rate (℃ / min) 2 2 5 5 Insulation time (h) 2 6 8 2 Annealing temperature(℃) 300 400 500 400
[0079] In order to illustrate the advancement and superiority of the method of preparing the net-shaped silver-coated magnetic metal by annealing in the present invention, a comparative example is provided for comparison and explanation.
[0080] Comparative Example 1
[0081] Comparative Example 1 was prepared with the same process parameters as Example 4 in Tables 1 to 4, but without annealing treatment.
[0082] Figure 2 This is the microscopic morphology of the silver-coated magnetic metal prepared in Example 4. It can be seen that the silver shell layer is coated on the surface of the magnetic metal in a mesh shape. Figure 3 This is the microscopic morphology of the silver-coated magnetic metal prepared in Comparative Example 1. It can be seen that the silver shell is accumulated on the surface of the magnetic metal in the form of nano-silver particles.
[0083] To illustrate the electromagnetic shielding effect of each embodiment and comparative example, 85 parts of silver-coated magnetic metal, 12 parts of H30 epoxy resin, 3 parts of polyamide curing agent, and 65 parts of xylene diluent were mixed and dispersed, and then an electromagnetic shielding coating with a thickness of 0.5 mm was prepared by air compression spraying.
[0084] In order to illustrate the electromagnetic shielding effectiveness of the prepared material, the electromagnetic shielding effectiveness was tested based on GJB 8820-2015 "Measurement Method for Shielding Effectiveness of Electromagnetic Shielding Materials", where 200kHz~30MHz was tested using the magnetic field method, and 30MHz~40GHz was tested using the electric field method. The results are shown in Table 6.
[0085] Table 6 Electromagnetic shielding effectiveness of various embodiments and comparative examples
[0086]
[0087] It can be seen from Table 6 that the shielding effectiveness of the embodiments of the present invention is greater than 65dB in the range of 30MHz to 40GHz, and greater than 30dB in the range of 200kHz to 30MHz, and has excellent shielding effect under ultra-wideband. The comparative example 1 is significantly lower than the embodiment 4 in each frequency band, which shows that the method of preparing the mesh silver-clad magnetic metal by annealing process in the present invention is superior.
[0088] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a mesh silver-coated magnetic metal electromagnetic shielding material, characterized in that: The following steps are involved: The magnetic metal powder is acid-washed to obtain acidified magnetic metal powder; The acidified magnetic metal powder is evenly dispersed in a Tris buffer solution, and then dopamine hydrochloride is added and the pH is adjusted to 8-9, and the reaction is carried out in the dark to obtain dopamine-coated magnetic metal powder; The dopamine-coated magnetic metal powder is uniformly mixed with deionized water, glucose, sodium potassium tartrate, and PVP, and then a silver ammonia solution is added to react with the mixture to obtain a silver-coated magnetic metal powder; Under vacuum, the silver-coated magnetic metal powder is heated to 200-600° C. and kept warm for 2-12 hours to obtain a mesh silver-coated magnetic metal electromagnetic shielding material.
2. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 1, characterized in that: The magnetic metal powder is one or more of iron-silicon-aluminum alloy, iron-silicon-chromium alloy, iron-silicon alloy, carbonyl iron, carbonyl nickel, iron-aluminum-boron alloy, iron-boron-phosphorus alloy, iron-nickel-molybdenum alloy, iron-chromium-nickel alloy, iron-nickel alloy, iron-cobalt-chromium alloy, and iron-cobalt-nickel-chromium alloy; The magnetic metal powder is a flaky magnetic metal powder obtained by ball milling, and its D50 is 2 to 65 μm.
3. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 1, characterized in that: The concentration of the Tris buffer solution is 0.05-0.25 mol / L; The mass ratio of the acidified magnetic metal powder, Tris buffer solution and dopamine hydrochloride is (25-60): (400-1000): (0.4-4); Among them, the light-avoidance reaction time is 12 to 48 hours.
4. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 1, characterized in that: The mass ratio of the dopamine-coated magnetic metal powder to deionized water, glucose, potassium sodium tartrate, PVP and silver ammonia solution is (20-80): (300-650): (2.3-28): (0.02-2.5): (0.5-4): (200-480); wherein the concentration of the silver ammonia solution is 7.5-80 g / L; and the addition rate of the silver ammonia solution is 50-250 ml / h.
5. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 4, characterized in that: The temperature of the mixed reaction is 20-60° C., and the reaction time is 0.2-4 hours.
6. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 1, characterized in that: The heating rate is 2-10°C / min.
7. The method for preparing the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 1, characterized in that: During pickling, the pH of the acid solution used is 1 to 3, and the pickling time is 3 to 10 minutes.
8. A mesh silver-coated magnetic metal electromagnetic shielding material obtained by the method according to any one of claims 1 to 7.
9. Use of the mesh silver-coated magnetic metal electromagnetic shielding material according to claim 8 in electromagnetic shielding.
Citation Information
Patent Citations
Method for preparing metal nanometer particles with hexagonal network in lattice distribution on substrate
CN102320557A
Silver-nickel composite electrical contact material with nickel distributed in net-shaped mode, and preparation method thereof
CN103996426A
Method for conducting surface chemical copper plating on inorganic particles through dopamine
CN105112894A
High-heat-conductivity silicone rubber thermal interface material containing magnetic metal fiber for LED and preparation method
CN106317882A
Preparation method of reticular gold-silver composite nanometer thin film
CN108330454A